DISCOVERY LEARNING (DL) STRATEGY ON STUDENTS READING COMPREHENSION IN REPORT TEXT - Mayang Sari; Tryanti R. Abdulrahman (Lingua, 2019)
This research entitled “Discovery Learning strategy on Grade Eleven Students’ Reading Comprehension in Report text at SMA Negeri 6 Karawang” principally aims to investigate whether or not DL strategy significantly affects on Students’Reading Comprehension. Research method used in this research was quasi experimental, quantitative and the design was randomized post-test only control group design.To collect data the writer used instruments in the form of objective, multiple choice 30 question items for sample class out of 60 questions items that have been tried out in IPS class on grade eleven at SMA Negeri 6 Karawang. The scores obtained from the try-out class were used to analyze the validity, reliability, discrimination power and difficulty index of each question items in the instruments. The sample of this research was grade eleven students in IPS class consisting of 60 students. The students is divided into two classes, 30 students in experimental class thought using DLstrategy and 30 in control class thought without DL strategy that are taken from the population using cluster random technique.The analysis using SPSS-based One Way Anova Formula produced significance (Sig.) value of 0.002, since the significance value was smaller than (<) Alpha 0.05, H0 is rejected and HAis accepted. It means that DL Strategy has significant effect on students’ reading comprehension.